2014
DOI: 10.1016/j.jrras.2014.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial gamma radiation dose measurement and health hazard along river Alaknanda and Ganges in India

Abstract: GangesAlaknanda Terrestrial gamma radiation Health hazard a b s t r a c t Direct measurement of absorbed dose rate in air due to exposure from outdoor terrestrial g radiation and assessment of consequent public health hazard continues to be of environmental and public concern. Present study was aimed to establish a baseline data of annual effective dose and to assess the associated health risk from outdoor terrestrial g radiation along the river Alaknanda and Ganges of India. Terrestrial g radiation exposure d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
3
7
0
Order By: Relevance
“…The variations in the mean TGRD values could be attributed to the parent materials from which the soils were derived. Soils, derived from acidic rocks (like granite) have higher TGRD contributions compared to soils derived from other rock types (Sharma et al, 2014) The results of this work were found to be in good agreement with those previously reported from different places with similar soil settings (Florou and Kritidis 1992; Garba et al, 2014;Garba et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…The variations in the mean TGRD values could be attributed to the parent materials from which the soils were derived. Soils, derived from acidic rocks (like granite) have higher TGRD contributions compared to soils derived from other rock types (Sharma et al, 2014) The results of this work were found to be in good agreement with those previously reported from different places with similar soil settings (Florou and Kritidis 1992; Garba et al, 2014;Garba et al, 2020).…”
Section: Resultssupporting
confidence: 91%
“…) and in India (0.375-0.662 x 10-3). 42,[46][47][48][49] The ELCR to the organs was however comparable to the value of 3.21x10 -3 obtained for Northern Pakistan where the researcher reported numerous deaths from cancer. 50 This again calls for further investigations for Nnewi and Anambra State with emphasis on the radionuclide contents of the soils.…”
supporting
confidence: 63%
“…However, the value of this index must be less than unity in order to keep the radiation hazard insignificant. The estimated values of excess lifetime cancer risk (ELCR) for all the samples from Table 3 ranged from 1.08 x 10 -4 to 1.46 x 10 -4 which is lower than world average of 2.9 x 10 -4 [19].…”
Section: Resultsmentioning
confidence: 78%